Disease Outbreaks in Understanding the Interpretation of the Qur'an (In the Case of Covid 19) - Dedi Masri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
As a believer, you will understand the meaning of contemplation to deal with the Corona Virus Covid-19, which is the first virus discovered in Wuhan, China in December 2019. We must be able to reflect on the stories that occurred during the Caliphate of Umar bin Khattab. The Qur'an reveals this story so that it can serve as a warning and a lesson to all believers. The wisdom in this calamity trial that can be taken is: 1. Allah SWT gives mercy and help to His servants who are believers, pious, pious and patient. 2. Believers are not spared from severe or light trials, as a test for them.